Black, green, and white tea infusions and powder forms improve oxidative stability of minced beef throughout refrigerated storage - Kirmizikaya, Gorkem; Karakaya, Mustafa; Babaoglu, Ali Samet (Wiley, 2021)
The effects of powder and infusions of white, black, and green teas on the physicohemical and sensory characteristics of minced beef during refrigerated storage for 7 days. Seven groups were prepared: control (C), powder and infusion forms of black (black tea powder [BTP] and black tea infusion [BTI]), green (green tea powder [GTP] and green tea infusion [GTI]), and white (white tea powder [WTP] and white tea infusion [WTI]) teas. Lipid oxidation (thiobarbituric acid reactive substances [TBARS]), antioxidant activity (2,2-diphenyl-1-picryl-hydrazyl-hydrate [DPPH]), pH, and color analyses were conducted on the first, third, fifth, and seventh days. The pH values of the samples increased with the progress of the storage and were found to be in the range of 5.44-5.86 throughout the storage. Different tea treatments significantly (p < .05) decreased the TBARS numbers of samples compared with control group. At the end of the storage, the lowest TBARS was found in the groups of GTI and WTI as 0.10 mg MA/kg sample. The highest DPPH values were found in WTP (50.50%-57.45%) during 7 days of storage. Practical applications Meat and meat products are prone to oxidation due to their protein and fat content. With the progress of oxidation, undesired rancid taste may occur in meat and meat products. Thus, nowadays, studies are carried out on using different natural additives to protect meat and meat products against oxidation. In this study, the effects of white, green, and black teas on antioxidative and sensory characteristics of fresh minced beef were investigated during refrigerated storage for 7 days. As a result, regarding lipid oxidation results and color properties, minced beef samples produced with different tea treatments had better quality in this study. This approach could be feasible in the production of minced beef in meat industry and homes.